Mathematics Beliefs of Secondary School Students: A Systematics Reviews - Lessa Roesdiana (EDUPEDIA PUBLISHER, 2023)
Purpose: This systematic review aims to explore the mathematics beliefs of secondary school students. Specifically, the study aims to identify the most commonly held mathematics beliefs by secondary school students and explore the factors that influence these beliefs. The review also aims to discuss the implications of the findings for educators and researchers. Methodology: The review included 27 studies, which were conducted between 2010 and 2021, and focused on mathematics beliefs of students in grades 7-12. The studies were conducted in various countries, including the United States, China, Turkey, and Iran. Findings: The results of the review suggest that mathematics beliefs of secondary school students are influenced by various factors, including gender, ethnicity, previous academic performance, teacher expectations, and cultural beliefs. Significance: Additionally, the review found that mathematics beliefs can impact students' academic achievement and their attitudes towards mathematics. Based on the findings of the review, recommendations for future research and educational practice are provided.